S67 Vitamin D deficiency drives pulmonary inflammation in a human model of the acute respiratory distress syndrome induced by inhaled lipopolysaccharide in healthy volunteers. (12th November 2015) - Fitzgerald, M; Shyamsundar, M; McNamee, JJ; Thickett, DR; O'Kane, CM; McAuley, DF
Abstract : The acute respiratory distress syndrome (ARDS) is characterised by exaggerated alveolar inflammation. Vitamin D deficiency in an LPS induced murine model of ARDS results in exaggerated alveolar inflammation. However the role of vitamin D deficiency in pulmonary inflammation in humans is unclear. We hypothesised that in healthy volunteers with vitamin D deficiency, pulmonary inflammation would be increased following LPS inhalation. Methods: Healthy volunteers inhaled 50 micrograms of LPS and six hours later underwent bronchoalveolar lavage for measurement of cytokines. Plasma was collected at baseline and one day post LPS inhalation for measurement of vitamin D. Results: 28 participants were included. The mean age of volunteers was 26.2 +/- 5.5 years. All 28 patients were vitamin D deficient (plasma levels <50 nmol/l), with 89% (25/28) patients having severe vitamin D deficiency (<25 nmol/l). Vitamin D levels were significantly higher after LPS inhalation (p < 0.002). Levels of IL-1β in BALF were significantly higher in those with severe deficiency than those with mild/moderate deficiency (Figure 1 ; p = 0.04). Levels of IL-6, IL-8 or TNF-α did not differ between groups. Conclusions: Vitamin D deficiency was highly prevalent in this population of healthy volunteers. The rise in vitamin D levels post LPS exposure may represent mobilisation of vitamin D from fat stores during inflammation though vitamin D metabolism and kinetics are complex and may differ in healthy volunteers and the critically ill. Severe deficiency correlated with increased alveolar inflammation.